2019
DOI: 10.1021/acssuschemeng.9b01644
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Ion Sensing by Structurally Simple Pyridine-End Oligo p-Phenylenevinylenes for Sustainable Detection of Toxic Industrial Waste

Abstract: Environmental pollution induced by toxic metal ions and harmful chemicals mainly from industrial waste poses a significant threat which urges for their rapid detection before release into the ecosystem above the permissible level. Optical sensors are inexpensive, simple, yet efficient in sensing such toxicants. Herein, we show that structurally simple π-conjugated pyridine-end p-phenylenevinylene oligomers can selectively sense toxic metal ions and anions in solution, supramolecular gels, as well as in solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Considering this, here, we devised low-cost, reusable paper strips for detection of E. coli (Figure a). , As expected, when the paper strips coated by probe 1 were treated with Cu 2+ , the color of the strips changed from orange to yellow, indicating the binding of the Cu 2+ ion to the carboxylic ends even in the solid state. To ensure the complete saturation of the paper strips with the Cu 2+ ion, the concentration of Cu 2+ in the eluent was varied along with the dipping time.…”
Section: Resultsmentioning
confidence: 73%
“…Considering this, here, we devised low-cost, reusable paper strips for detection of E. coli (Figure a). , As expected, when the paper strips coated by probe 1 were treated with Cu 2+ , the color of the strips changed from orange to yellow, indicating the binding of the Cu 2+ ion to the carboxylic ends even in the solid state. To ensure the complete saturation of the paper strips with the Cu 2+ ion, the concentration of Cu 2+ in the eluent was varied along with the dipping time.…”
Section: Resultsmentioning
confidence: 73%
“…Recently, Bhattacharya and coworkers showed that π-conjugated p-phenylenevinylene oligomers with a pyridine unit as the end group can selectively detect Hg 2+ . 29 Addition of Hg 2+ caused a distinct change in the color of CP-9 solutions from colorless to yellow accompanied by the transformation of the fluorescence from blue to intense yellow. Owing to the interaction of Hg 2+ with the nitrogen-containing pyridine moiety, the polymers can form two-coordination complexes.…”
Section: Mono-pyridine-based Cp Chemosensorsmentioning
confidence: 98%
“…Toxic industrial contaminants such as Cu 2+ and CN − are responsible for inducing pollution and life-threatening ailments owing to their careless release into the environment beyond their permissible limit. 1,2 Therefore, the detection of these water pollutants via molecular recognition is a fascinating and active research area due to the pivotal role exhibited by these ions in biological and industrial processes, pharmaceuticals, and environmental and human sciences. Cu 2+ is an essential d 9 metal ion, playing an indispensable role in various physiological metabolisms.…”
Section: Introductionmentioning
confidence: 99%